Design and fabrication of printer table - Hadianatun Saadiah, Jasni (2013)
Creativity of idea is very important in designation.It is because, idea very important to produce a quality, interesting and unique product.As a new product for customer, this printer table is design followed need characteristic such as easy to handle, multifunction and attractive.In this project, main objective is to create and design a new product based on the existing product in the market. This project are using of various kind of mechanism that have in mechanical laboratory such as aluminum square hollow rod, wheel, welding, rivet and sheet metal. These printer table projects are need multiple method like measurement, marking, cutting, joining and assembly process.This process are important because its involve student skill of using a tool and machine.Besides that, it also can make a student learn something new to increase a creativity of thinking and think to produce interesting product for the future market.This product also must have a characteristic like toughness.It also must be analysis at first to know its strength and what the problem happened on this product. These projects make the student more discipline, punctuality, create a leadership skills and have a good planning in order that can practice it in real situation at the work place.